Physical Layer Security of Hybrid Satellite-FSO Cooperative Systems - Yun Ai; Aashish Mathur; Michael Cheffena; Manav R. Bhatnagar; Hongjiang Lei (IEEE Photonics Journal)
In this paper, we study the physical layer secrecy performance of a hybrid satellite and free-space optical (FSO) cooperative system. The satellite links are assumed to follow the shadowed-Rician fading distribution, and the channel of the terrestrial link between the relay and destination is assumed to experience the gamma–gamma fading. For the FSO communications, the effects of different types of detection techniques (i.e., heterodyne detection and intensity modulation with direct detection) as well as the pointing error are considered. We derive exact analytical expressions for the average secrecy capacity and secrecy outage probability (SOP) for both cases of amplify-and-forward (AF) and decode-and-forward (DF) relaying. The asymptotic analysis for the SOP is also conducted to provide more insights on the impact of FSO and satellite channels on secrecy performance. It is found that with the AF with fixed gain scheme, the secrecy diversity order of the investigated system is only dependent on the channel characteristics of the FSO link and the FSO detection type, whereas the secrecy diversity is zero when the relay node employs DF or AF with variable-gain schemes.